2013
DOI: 10.2478/pomr-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

A new planning model to support logistics service providers in selecting mode, route, and terminal location

Abstract: In this paper, we address thefreight network design problem. A mixed integer linear program is formulated to help logistics service providers jointlyselect the best terminal locations among a set of candidate locations, shipping modes, and route for shipping different types of commodities. The developed model isapplied to two different networksto show its applicability. Results obtained from CPLEX for the case studiesare presented, and the benefit of the proposed model is discussed.Key words: Intermodal transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The previous research found that route selection is a fundamental problem of multimodal transportation and logistics management [17,18]. A large number of literature has been published in the area of multimodal route selection.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research found that route selection is a fundamental problem of multimodal transportation and logistics management [17,18]. A large number of literature has been published in the area of multimodal route selection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem is formulated by using Eqs. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The significant weights obtained using the AHP method in the previous phase are added into the objective function of ZOGP.…”
Section: Zero-one Goal Programingmentioning
confidence: 99%
See 1 more Smart Citation
“…Deterministic models [1,5,9-11,13,14,17,25-27,32] Stochastic/fuzzy models [3,7,8,12,15,16,34,42,48,49] Exact methods [1,7,8,11,25] heuristic methods [10,12,15,27,32,50] To our knowledge, we are the first to build a model for an intermodal transportation network considering the general case when the induced graph by the located rail terminals is an incomplete graph. The proposed model is a mixed linear program that provides optimal solutions to achieve a balanced intermodal network.…”
Section: Research Type Referencesmentioning
confidence: 99%
“…Other studies have modeled transit hub capacity limits but did not consider the congestion effect (15,16). Some studies considered only transshipment costs (the second need) without factoring congestion costs (17)(18)(19)(20). For shippers, the costs of both transshipment and delay can significantly affect transportation decisions.…”
Section: Dynamic Model For System-level Strategic Intermodal Facility Investment Planningmentioning
confidence: 99%